MISSING THE ESSENCE OF CONSENT IN PERSONAL GUARANTEES IN ONLINE LOAN PRACTICES - Muljono, Bambang Eko; Suisno; Sastradinata, Dhevi Nayasari; Asror, Nabil Al (Jurnal Independent, 2022)
Abstract Related to the problem of online loans that no longer heed the approval of third parties in appointing someone as a guarantor of the debtor's debt. Then the novelty will be offered as a solution to the existing problems by using a research method in the form of normative juridical which of course will be guided by the applicable laws miand regulations related to the problems that arise and other legal materials that are still relevant. In the economic sector, especially in non-bank financial institutions that provide online loan services, also use the internet as the main media. Seeing the facts that occur, namely regarding the rise of online loans as a creditor who makes a third party a guarantor of the debtor, outside the knowledge and without the consent of someone who becomes a third party, makes the public question how the government, especially those related to the financial sector, handles these cases. Especially for the Financial Services Authority (OJK), which has the authority and duty to supervise various non-bank financial institutions that have been regulated to be outside the authority of Bank Indonesia to supervise them. Because of these complicated problems, researchers are interested in researching further.